Pengaruh Manajemen Sumber Daya Manusia Terhadap Kinerja Karyawan Rumah Sakit Hermina Pekalongan - Siti Pattihatun; Arif Budiharjo (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this study is to test and analyze the influence of human resource management on employee performance at Hermina Pekalongan Hospital. This study uses a simple random sampling method with a sample number of 32. This study used 4 independent variables and 1 dependent variable. Data analysis techniques involve validity tests, reliability tests, classical assumption tests, multiple linear regressions, and hypothesis tests. Recruitment and Selection have no influence on employee performance. Training has a positive and significant influence on employee performance. HR Compensation and Maintenance have no effect on employee performance. Employee training is the only independent variable that has an influence on employee performance.